2017
DOI: 10.1016/j.jcot.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

India contribution to Spine Surgery: 15 most influential articles

Abstract: There are an increasing number of papers from India in the field of spine surgery literature. Most of the highly cited papers were related to tuberculosis. We expect further contributions from our country to the medical literature in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Similar to the findings of Sinan et al in our study, it most often concerned the lumbar vertebrae, followed by the thoracic vertebrae. In a study by Sinan et al, he found involvement of intervertebral disc in 74% of cases, and in our study, there was 86.7% of them [23][24] . Gibbus, which transpires mainly in the dorsal spine, was seen in 28.2% of the patients testified in only 1/3 rd of the patients in the African study 25 .…”
Section: Discussionsupporting
confidence: 62%
“…Similar to the findings of Sinan et al in our study, it most often concerned the lumbar vertebrae, followed by the thoracic vertebrae. In a study by Sinan et al, he found involvement of intervertebral disc in 74% of cases, and in our study, there was 86.7% of them [23][24] . Gibbus, which transpires mainly in the dorsal spine, was seen in 28.2% of the patients testified in only 1/3 rd of the patients in the African study 25 .…”
Section: Discussionsupporting
confidence: 62%